Anfibatide protects against rat cerebral ischemia/reperfusion injury via TLR4/JNK/caspase-3 pathway - Luo, Sheng-Yong; Li, Rui; Le, Zhi-Yong; Li, Qing-Lin; Chen, Zhi-Wu (European journal of pharmacology, 2017)
Anfibatide (ANF) is a GPIb antagonist derived from the protein complex agglucetin. Previous studies have showed that it has protective effect on cerebral ischemia/reperfusion injury, the mechanism of which is still unclear, however. The present study was designed to investigate the protective effect of ANF on cerebral I/R injury in rats and the possible mechanisms. Focal cerebral ischemia was induced by 90min of transient middle cerebral artery occlusion (MCAO). ANF (1, 2, 4μg/kg) was achieved by intravenous injection after 120min of MCAO followed by 1h, 24h ,48h and 72h reperfusion. Neurological deficit, infarct volume, histopathology, neuronal apoptosis, NeuN and the expression of TLR4, total and phosphorylated c-Jun NH2-terminal kinase (JNK/p-JNK), Bcl-2, Bax, caspase-3, NF-κB protein in rat brain, the levels of IL-1β, IL-6 and TNF-α in serum were evaluated 72h after reperfusion. ANF could significantly decrease neurological score, reduce the infarct volumes, ameliorate the histopathological alteration, attenuate the neuronal apoptosis and increase the fluorescence density of NeuN in the rat brain. Furthermore, ANF could obviously decrease the expression of TLR4, p-JNK, caspase-3, NF-κB , relative ratio of Bax/Bcl-2 in brain and the levels of IL-1β, IL-6 and TNF-α in serum. The results indicate that ANF has protective effect against cerebral I/R injury in rats and the underlying mechanism may be associated with the suppression of apoptosis through inhibiting TLR4/JNK/caspase-3 signaling pathway. [Display omitted]